Synergistic technology combinations for future commercial aircraft using liquid hydrogen - Rompokos, Pavlos; Rolt, Andrew Martin; Nalianda, Devaiah; Isikveren, Askin T.; Senné, Capucine; Gronstedt, Tomas; Abedi, Hamidreza (American Society of Mechanical Engineers (ASME), 2021)
Liquid hydrogen (LH2) has long been seen as a technically feasible fuel for a fully sustainable greener aviation future. The low density of the cryogenic fuel would dictate the redesign of commercial aircraft to accommodate the large tanks, which are unlikely to be integrated within the whole internal volume of the wing. In the ENABLEH2 project, the morphological aspects of a LH2 aircraft design are discussed and a methodology for rapid concept comparative assessment is proposed. An exercise is then carried on to down-select short-to-medium range (SMR) and long-range (LR) concepts, able to carry 200 passengers for 3000 nmi and 414 passengers for 7500?nmi respectively. The down-selection process was split into two phases with the first considering 31 potential airframe architectures and 21 propulsion-system arrangements. The second phase made the final down-selections from a short-list of nine integrated design concepts that were ranked according to 34 criteria, relating to operating cost, revenue, noise and safety. Upon completion of the process, a tube and wing design with the tanks integrated into extended wing roots, and a blended-wing-body design were selected as the best candidates for the SMR and LR applications respectively. Both concepts feature distributed propulsion to maximise synergies from integrating the airframe and propulsion systems.
Keywords: Aircraft; Hydrogen; Design; Wings; Fuels; Propulsion systems; Architecture; Aviation; Density; Noise (Sound); Propulsion; Safety; Sustainability